2006
DOI: 10.1303/aez.2006.357
|View full text |Cite
|
Sign up to set email alerts
|

Role of host plant volatile in the host-finding behavior of the strawberry leaf beetle, Galerucella vittaticollis Baly (Coleoptera: Chrysomelidae)

Abstract: The strawberry leaf beetle, Galerucella vittaticollis Baly, is an oligophagous insect that feeds on strawberry and polygonaceous plants. (Gramineae). The main component of the headspace of all host plants tested was one of the green leaf volatiles, cis-3-hexenyl acetate. This compound was detected also in the non-host plants except T. aestivum. However, its relative content in A. princeps or L. chinense was different from that in host plants. The headspace of R. sativus contained one of the isothiocyanates, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Another report indicated the phenyl acetaldehyde significantly increased the number of male S. litura attracted to the pheromone at a suitable concentration (Shen et al, 2009). An important plant volatile, cis-3-Hexenyl acetate, as an olfactory cue, exclusively attracts herbivorous insects to find the host plants (Peacock et al, 2001;Hori et al, 2006) and it significantly attracts females of several moth species (Reddy & Guerrero, 2000;Dai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another report indicated the phenyl acetaldehyde significantly increased the number of male S. litura attracted to the pheromone at a suitable concentration (Shen et al, 2009). An important plant volatile, cis-3-Hexenyl acetate, as an olfactory cue, exclusively attracts herbivorous insects to find the host plants (Peacock et al, 2001;Hori et al, 2006) and it significantly attracts females of several moth species (Reddy & Guerrero, 2000;Dai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many phytophagous insects, including mirid bugs, use host plant odors as olfactory cues to find hosts (Visser, 1986;Groot et al, 2003;Blackmer et al, 2004;Hori, 1999;Hori et al, 2006). In previous studies, we investigated the behavioral responses of rice leaf bugs to rice plant odors with a linear track olfactometer.…”
Section: Introductionmentioning
confidence: 99%
“…However, for Ceratitis capitata (Wiedemann), the presence of trans-2-hexenal did increase female response to male odor (Dickens et al 1990). Conversely, the chrysomelid strawberry leaf beetle, Galerucella vittaticollis Baly, is not attracted to this compound, but is attracted to another green leaf volatile, cis-3-hexenyl acetate in the Þeld (Hori et al 2008). Our results indicated that this green leaf volatile could be repellent to plum curculio based on numerically lower injury in trap trees augmented with this stimulus compared with standard trap trees (results reported here and also based on Prokopy et al 2003) and from previous laboratory studies demonstrating repellency at high concentrations .…”
Section: Discussionmentioning
confidence: 99%